First species of Cunaxa (Acari: Cunaxidae) from Brazil - Wurlitzer, Wesley Borges; Ferla, N. J.; Franklin, E.; Liberato da Silva, Guilherme; Dos Santos Rocha, Matheus (Systematic and Applied Acarology, 2021)
Two new species, namely Cunaxa jacobdenheyeri Wurlitzer & Silva sp. nov. and Cunaxa butantorum Wurlitzer & Rocha sp. nov. are illustrated and described. Cunaxa jacobdenheyerisp. nov. resembles Cunaxa heterostriataKhaustov & Kuznetzov, 1998, C. jatoiensisBashir & Afzal, 2006, C. polita Kazmierski & Ripka, 2015, in Ripka et al. 2015, C. subita Ripka & Laniecka, in Ripka et al. 2015 and C. minuta Laniecka & Kazmierski, in Ripka et al. 2015. It differs from previous species by possessing the hysterosoma with a shield bearing c2, c1-e1, by the telofemoral apophysis straight, and by chaetotaxy of the genua II with and pseudanal setae ps2 absent. Cunaxa butantorumsp. nov. resembles C. setirostris (Hermann, 1804), in Den Heyer & Sergeyenko, 2009, C. potchensisDen Heyer, 1979 and C. neogazellaSmiley, 1992. It differs by previous species by having the propodosomal shield partially covered by broken striae, by chaetotaxy of the genu I, II and by apophysis on palp telofemur long. © 2016 EDP Sciences. All rights reserved.